„В хорошем” или „в плохом смысле” — об одном из способов вербализации акта оценки - Paulina Bortnowska (Studia Rossica Posnaniensia)
Structures in the good sense and in the bad sense are one of the ways of verbalizing the act of evaluation. What is interesting from the psycholinguistic point of view is their potential to activate a “backward” evaluation of concepts that are well established in the system of language that lies hidden in these structures, on the one hand, and the elements of the dynamics of axiomatic processes in the language that reflect social and cultural changes that can be revealed by them, on the other hand.